A Stable Porphyrin Functionalized Graphite Electrode Used at the Oxygen Evolution Reaction Potential. Issue 7 (22nd January 2022) - Bussetti, Gianlorenzo; Bernasconi, Roberto; Filoni, Claudia; Magagnin, Luca; Bossi, Alberto; Ciccacci, Franco; Duò, Lamberto
Abstract: Many researches have been devoted to rechargeable power generators that can store (but also release) energy. This availability is ensured through ( e. g .) the oxygen evolution reaction (OER). However, (i) large values of the overpotentials and (ii) a progressive detriment of the anode (graphite) electrode limit the ultimate device. In view of enhancing the electrode performances, graphite was protected by following different strategies, which oblige to follow precise preparation protocols. Here, we prove that a thin layer of free‐base porphyrin molecules is able to protect the underneath graphite electrode from detriment even if many (about 100) electrochemical cycles are performed. Abstract :